2004
DOI: 10.1007/s00412-004-0281-9
|View full text |Cite
|
Sign up to set email alerts
|

The enhancement of histone H4 and H2A serine 1 phosphorylation during mitosis and S-phase is evolutionarily conserved

Abstract: Histone phosphorylation has long been associated with condensed mitotic chromatin; however, the functional roles of these modifications are not yet understood. Histones H1 and H3 are highly phosphorylated from late G2 through telophase in many organisms, and have been implicated in chromatin condensation and sister chromatid segregation. However, mutational analyses in yeast and biochemical experiments with Xenopus extracts have demonstrated that phosphorylation of H1 and H3 is not essential for such processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
101
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 42 publications
(49 reference statements)
8
101
2
Order By: Relevance
“…It is clear that me 3 H3K9, me 3 H4K20 and HP1γ are present in all cell states, with no obvious changes in amounts. Also shown are two phosphorylated histone "mitotic" markers, [29][30][31] H3(S10)phos and H4/H2A(S1)phos, which also reveal no significant or systematic changes when comparing the various cell forms.…”
Section: Heterochromatin Markers In Epro Cell Linesmentioning
confidence: 95%
“…It is clear that me 3 H3K9, me 3 H4K20 and HP1γ are present in all cell states, with no obvious changes in amounts. Also shown are two phosphorylated histone "mitotic" markers, [29][30][31] H3(S10)phos and H4/H2A(S1)phos, which also reveal no significant or systematic changes when comparing the various cell forms.…”
Section: Heterochromatin Markers In Epro Cell Linesmentioning
confidence: 95%
“…In all three analyses, the ion intensities of acetylated peptides were decreased in S phase, and most of these ions were absent in G 2 /M phase. For the monoacetylated H2BJ/N and H2BA variants, MS/MS analysis of the corresponding peptides localized acetylation on Lys 12 , Lys 15 , and Lys 20 (Supplemental Figs. 16 and 18 and Ref.…”
Section: General Strategy Of Ms Analysis Of Histones Frommentioning
confidence: 99%
“…Recent reports have shown that H3 is also phosphorylated at Ser28, Thr11, Thr3, and H3.3 Ser 31 during mitosis (11)(12)(13)(14). For histones H4 and H2A, hyperphosphorylation was detected at their respective Ser 1 residues during mitosis in worm, fly, and mammalian cells (15). For histone acetylation, one of the better understood histone modifications, it is now generally accepted that hyperacetylated histones are mostly associated with activated genomic regions, whereas deacetylation mainly results in repression and silencing (16,17).…”
mentioning
confidence: 99%
“…However, mutations altering S10 of H3 do not alter mitosis, meiosis, or cell growth, suggesting a possible redundancy of its function (Hsu et al 2000;Barber et al 2004).…”
mentioning
confidence: 99%
“…Although H3 S10 is a common mitotic/meiotic histone phosphorylation mark correlated with chromatin condensation, mutations that alter H3 S10 do not effect either mitosis or meiosis (Barber et al 2004). Therefore, Krishnamoorthy et al (2006) sought to determine whether an H4 S1A mutation demonstrates defects in sporulation.…”
mentioning
confidence: 99%